Scanning the horizon of personalized prevention research: an overview of ongoing European funded initiatives - Maio, Alessandra; Farina, Sara; Osti, Tommaso; Di Grande, Salvatore; Pastorino, Roberta; Boccia, Stefania (Frontiers in Public Health, 2025)
IntroductionNon-communicable diseases represent a significant burden on global healthcare, necessitating innovative strategies to enhance prevention and management. Personalized prevention, an emerging approach leveraging omics data to tailor interventions, holds promise for improving risk stratification, early diagnosis, and preventive strategies. To gain insights on the latest funding investments in this field, we mapped European Commission (EC)-funded research projects on personalized prevention for non-communicable diseases.Materials and methodsWe carried out a scoping review of gray literature sources, following the Arksey and O’Malley framework, combined with expert consultations to validate findings and address data gaps. Inclusion criteria focused on projects that began or were ongoing in 2024 (from January 1st to December 31st).ResultsWe identified 67 projects supported by a total amount of €511.9 million from EC funding. The main programs include Horizon Europe, Horizon 2020, and EU4Health. In particular, Horizon Europe funds 51% of these projects, with a total allocation of €253.8 million, 44% of which specifically address cancer. Overall, 48% of the projects target cancer, followed by neurological and psychiatric diseases (15%), cardiovascular diseases (13%), metabolic disorders (9%), and other NCDs (16%). In terms of prevention levels, 21% of the projects are dedicated to primary prevention, 41% to secondary prevention, and 38% to tertiary prevention.ConclusionThe EC’s investment in personalized prevention is predominantly directed toward cancer, reflecting the goals of the Cancer Mission and the European Beating Cancer Plan. Research on tertiary prevention remains less prominent, likely due to its already established clinical applications, while the emphasis on primary and secondary prevention is reassuring, considering the current gaps in clinical utility evidence in these areas.